A review of the characters of nanofluids used in the cooling of a photovoltaic -thermal collector - Maseer M.M.; Alnaimi F.B.I.; Hannun R.M.; Chin Wai L.; Al-Gburi K.A.H.; Mezan S.O. (Elsevier Ltd, 2023)
Alumina; Aluminum oxide; Copper oxides; II-VI semiconductors; Magnesia; Nanofluidics; Silica; SiO2 nanoparticles; Thermal conductivity of liquids; TiO2 nanoparticles; Titanium dioxide; Zinc oxide; Base nanofluid; Biphasic systems; Colloidal dispersion; Density and viscosity; Hybrid; Nanofluids; Photovoltaic thermals; Thermal collectors; Thermal Performance; Viscosity